Unbridling Barriers to Communication: Saddling Mand Training & EAAT Therapy Together - Autry, Faye (My University, 2020)
This study reviews the current research on applied behavior analysis (ABA) and equine-assisted activity and therapy (EAAT) for individuals with autism spectrum disorder (ASD) on verbal communication behavior. Research on ABA interventions for verbal behaviors has shown substantial increases in verbal operant(s) such as manding with children with ASD. EAAT intervention studies regarding communication to include manding behavior have also shown promising increases with children with ASD. This study used a multiple baseline design across participants to establish whether there is a functional relation between mand training integrated in a specific type of EAAT (Equine-Assisted Learning or EAL) activity and manding behaviors in individuals with ASD. Keywords: mand training, interrupted chain procedure, applied behavior analysis, ABA, autism spectrum disorder, ASD, behavior, combining, equine-assisted therapy, EAAT, EAL manding, verbal, communication, single case, multiple baseline design
Keywords: applied behavior analysis; equine-assisted therapy; mand training; autism spectrum disorder